Effect of oxidative stress on kidney cortex angiotensinogen expression in rate type 1 diabetes model - ZHENG Wei-ping; LIANG Xiang; ZOU Yuan-fang; LIU Yu-feng; SU Xiao-yan (Linchuang shenzangbing zazhi)
Objective To observe the changes of kidney cortex angiotensinogen(AGT)expression in rate typeⅠ diabetes model,and the effect of the anti-oxidative stress induction on the kidney cortex AGT expression in order to infer indirectly that there is some relationship between renin-angiotensin system(RAS)and oxidative stress.Methods First part of the experiment:Male Sprague Dawley(SD)rats were randomly divided into two groups:diabetic mellitus(DM)group and non-DM group.Rats in DM group were injected with streptozotocin(STZ)intraperitoneally,and those in nonDM group were given the same dosage of vehicle.The body weight,blood glucose,blood pressure and AGT expression in both groups were measured at the end of 4 weeks.Second part of the experiment:All typeⅠ diabetes rats were randomly divided into four groups,and administrated with distilled water,Losartan,hydralazine and Tempol respectively.The body weight,blood glucose,blood pressure and AGT expression in all groups were detected after 4 weeks since the typeⅠ diabetes model was established.Results There were significant differences in body weight,blood glucose and blood pressure between non-DM group and DM group after 4 weeks(P<0.05).The cortex AGT expression was up-regulated in DM group.There was no significant difference in body weight,blood glucose and blood pressure among the four groups.The cortex AGT expression in Losartan group and Tempol group was reduced significantly,and that in hydralazine group had no changes as compared with the distilled water group.Conclusions The cortex AGT expression was up-regulated in DM group.Both anti oxidative stress and Losartan can reduce the AGT expression,suggesting some relationships between the activity of RAS and oxidative stress.